A Report on the Illegal Treatment of Farm Workers in California 1967 - American Friends Service Committee::::::; Michael Bennett::::::; Peter Lauwerys::::::; Christopher Paige:::::: (1967)
A report examining the treatment of farm workers and the conditions they reside in.